2020
DOI: 10.1055/a-1033-9588
|View full text |Cite
|
Sign up to set email alerts
|

Cycle-related Diarrhea and Dysmenorrhea are Independent Predictors of Peritoneal Endometriosis, Cycle-related Dyschezia is an Independent Predictor of Rectal Involvement

Abstract: Introduction The clinical presentation of endometriosis is extremely varied. Because endometriosis symptoms may overlap with symptoms caused by gastroenterological disorders, this can lead to misdiagnosis and a considerable delay in arriving at the correct diagnosis. The aim was to evaluate the type and duration of endometriosis-related symptoms and to identify predictors for patterns of involvement depending on symptoms. Material and Method The data of 266 consecutive patients who were operated on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Haas et al showed that women with endometriosis in ENZIAN compartment C, which corresponds to our Group 3, were more likely to report gastrointestinal symptoms (24). In a recent retrospective series of 266 women, cycle-related dyschezia was independently associated with rectal involvement (25). In a recent study that evaluated the association between preoperative symptoms and revised ENZIAN classification, dyschezia was significantly correlated with rectal involvement corresponding to the ENZIAN C compartment (26).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Haas et al showed that women with endometriosis in ENZIAN compartment C, which corresponds to our Group 3, were more likely to report gastrointestinal symptoms (24). In a recent retrospective series of 266 women, cycle-related dyschezia was independently associated with rectal involvement (25). In a recent study that evaluated the association between preoperative symptoms and revised ENZIAN classification, dyschezia was significantly correlated with rectal involvement corresponding to the ENZIAN C compartment (26).…”
Section: Discussionmentioning
confidence: 52%
“…In a prospective study, women with superficial endometriosis reported several cycle-related digestive symptoms with frequency ranges between 5-43% (13). In another retrospective study, cycle-related diarrhoea was significantly associated with superficial peritoneal endometriosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Around 10% of women aged 15 – 50 years suffer from dysmenorrhea, dyspareunia, abdominal and pelvic pain as well as infertility and are diagnosed with endometriosis 1 . The presentation of symptoms in women with endometriosis is suggestive for the location of the endometriotic lesions and the clinical stage 2 , but up to now, the definitive diagnosis of endometriosis needs surgery. Serum markers for endometriosis are being investigated but have not yet been clinically established 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Up to 50% of women with pelvic pain and/or infertility and 10–15% of reproductive-aged women have endometriosis [ 6 ]. Endometriosis symptoms include infertility, dysmenorrhea, pelvic pain, dyspareunia, mittelschmerz, back pain, dysuria, dyschezia, abundant irregular menstruation, gastrointestinal problems (diarrhea or constipation), hematochezia, and chronic fatigue [ 7 , 8 , 9 ]. Adhesions, organ damage, and fibrosis are the main causes of infertility and pain in endometriosis’ severe phases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%